Minimum leaf conductance during drought: unravelling its variability and impact on plant survival - Burlett, Régis; Trueba, Santiago; Bouteiller, Xavier Paul; Forget, Guillaume; Torres‐Ruiz, José M.; Martin‐StPaul, Nicolas K.; Parise, Camille; Cochard, Hervé; Delzon, Sylvain (The New phytologist, 2025)
Summary Leaf water loss after stomatal closure is key to understanding the effects of prolonged drought on vegetation. It is therefore important to accurately quantify such water losses to improve physiology‐based models of drought‐induced plant mortality. We measured water loss of detached leaves continuously during dehydration in nine woody angiosperm species. We computed minimum leaf conductance (gmin) at different water potential thresholds along a sequence of physiological function losses, spanning from turgor loss point to hydraulic failure. A mechanistic model evaluated the impact of different gmin estimations on the time to hydraulic failure (THF). Residual conductance is not steady and decreases continuously at varying rates across species during the entire dehydration process, even after correcting for leaf shrinkage and vapor pressure deficit shifts. Different estimations of gmin had a significant impact on the THF predicted by the model, especially for drought‐resistant species. We demonstrate that residual conductance is variable during dehydration, and thus, it is important to use physiological or water status boundaries for its estimation in order to determine distinct gmin values of water loss. We describe an accurate, repeatable and open‐source methodology to estimate gmin. Such methodology could enhance models of plant mortality under drought. Résumé L’étude de la perte d’eau des feuilles après la fermeture des stomates est essentielle pour comprendre les effets d’une sécheresse prolongée sur la végétation. Il est donc important de quantifier précisément ces pertes pour améliorer les modèles de mortalité des plantes induite par la sécheresse. Nous avons mesuré en continu la perte d’eau de feuilles détachées pendant la déshydratation chez neuf espèces d’angiospermes et calculé la conductance foliaire minimale (gmin) à différents seuils de potentiel hydrique correspondants aux seuils de pertes de fonctions physiologiques, allant du point de perte de turgescence à la défaillance hydraulique. Un modèle mécaniste a évalué l’impact des différentes estimations de gmin sur le temps de défaillance hydraulique (THF). La conductance résiduelle n’est pas stable et diminue continuellement à des rythmes variés d’une espèce à l’autre pendant toute la durée du processus de déshydratation, même après correction du rétrécissement des feuille. La prise en compte des variations de l’estimations de gmin a un impact significatif sur le THF prédit par le modèle, en particulier pour les espèces résistantes à la sécheresse. Nous démontrons que la conductance résiduelle est variable au cours de la déshydratation, et qu’il est donc important de préciser pour quelles limites physiologiques ou état hydrique l’estimation de gmin a été effectué. Nous décrivons une méthodologie précise, reproductible et open‐source pour cette estimation. Une telle méthodologie pourrait améliorer les modèles de mortalité des plantes lors de sécheresse.